The Inheritable Characteristics of Monoecy and Parthenogenesis Provide A Means for Establishing A Doubled Haploid Population in the Economically Important Brown Alga Undariapinnatifida (Laminariales, Alariaceae). Issue 3 (2nd April 2021) - Shan, Tifeng; Pang, Shaojun; Wang, Xuemei; Li, Jing
Abstract : Monoecy and parthenogenesis exist in certain male and female gametophytes of the brown alga Undaria pinnatifida . The inheritance of these traits is not known. In this study, we made a cross between a male and a female gametophyte clone which could exhibit monoecy and parthenogenesis phenotypes, respectively, and obtained their next‐generation gametophyte offspring. We found that under conditions suitable for gametogenesis, all of the male offspring ( n  = 100) exhibited monoecy phenotype and all of the female offspring ( n  = 100) only formed oogonia and underwent parthenogenesis, suggesting that monoecy and parthenogenesis phenotypes are inheritable. Then, we established a doubled haploid (DH) population through monoecious selfing and parthenogenesis, and evaluated the young sporophyte growth and the maximum quantum yield ( F v / F m ) of 10 "male" and 10 "female" DH lines. On day 60, the average length of the "male" DH lines was significantly larger than that of the "female" DH lines, while their average F v / F m values were not significantly different. Monoecious selfing seemed superior to parthenogenesis as the sporophyte formation efficiency, and the young sporophyte growth was better in the former than in the latter. We also crossed two monoecious gametophytes with another male gametophyte, and a parentage analysis showed success of obtaining hybrid sporophytes, indicating that the female gametes released by the monoecious gametophyte can actually be fertilized by sperm. The approach of establishing a DH population proposed here will be useful in genetic breeding and quantitative trait loci mapping in U. pinnatifida and may be applicable to other kelp species.